SPEECH STYLE OF JOKO WIDODO AT APEC CEO SUMMIT 2014 - Nida Hayun Fadila; Aris Wuryantoro; Lusia Kristiasih Dwi Purnomosasi (Universitas PGRI Madiun, 2016)
Communication is something that to share their feeling, opinion, information, and etc to other people. In communication, they can use some variations of language when they talk to other people. That is what is called as style. Style can occur in written spoken and discourse. The style that occurs in spoken discourse is called speech style. The research is conducted to know type speech style and rhetorical strategies of Joko Widodo in APEC CEO Summit 2014. The objectives of this research are: (1) describing the type of speech style used by Joko Widodo in his speech in APEC CEO Summit 2014 and (2) analyzing rhetorical strategies in Joko Widodo speech in APEC CEO Summit 2014. The approach of the research is qualitative. Essentially, the research is descriptive qualitative. The data of the research is documentation of Joko Widodo’s speech in APEC CEO Summit 2014. Analyze data technique used by researcher is descriptively and analytically: surveys and fact – finding enquiries of different kinds and analyze these to make a critical evaluation of the material. The results of the research show: (1) the types of: formal style (45.2 %), consultative style (46.6 %), and casual style (8.2%). the highest type used by Joko Widodo is consultative style and (2) in rhetorical strategies used by Joko Widodo using three types modes persuasion. The types of: Ethos (35.6 %), pathos (15 %), and logos (49.4%). The highest type used by Joko Widodo is Logos. Joko Widodo mostly using consultative style and logos in his speech because he is mostly doing semi – formal acrtivity than formal activity